SERBUK BAMBU SEBAGAI ALTERNATIF BAHAN DASAR TINTA BRAILLE - dan Sri Lastuti, Erna Wiji Astuti, Fifit Astuti, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
The aims of this research are to find out the way to make proper compositionin making Braille ink using bamboo extract as an alternative basic material, toknow the quality of Braille ink using bamboo extract and to know the effectivenessof Braille ink made from bamboo extract to assist blind people in reading Brailleor Arabic letter like the normal one.This research belongs to an experimental research. The population of thisresearch was China ink. "Tinta Bak", a China ink, was chosen as the sample ofthe supplementary material of making Braille ink in which bamboo extract wasthe main material. The free variables of this research were bamboo extract content,alcohol and some other needed supplementary materials. The bound variableswere the proper composition of the ink and the test result of its use. Theinstruments used in this research were scale, cup, mixer, blender, graduatedglass, test-tube, Erlenmeyer tube, bunsen and dripped pipette. The materialsused in this research were China ink, bamboo extract, alcohol, glycerine, Arabicgom, and aquades. The data were the result of experiment on the compatibilityof ink content and the result of its use. Then, they were analyzed to know thecomposition of ink and the best use and the quality of Braille ink using bambooextract as the basic materials.The result of the research shows that the mixture among Arabic gom,glycerine, aquades, china ink and bamboo extract can be used to make a goodquality of Braille ink. The ideal Braille ink can be produced if it fulfils somecharacteristics, namely, having enough thick consistency; not dry soon, andhaving appearing effect, thus it can touched with fingers.Key words: Braille ink, bamboo extract